The Position and Role of the Supreme Court in Fostering Religious Courts as Part of the National Legal System: (Review of PERMA Number 5 of 2019) - Afiful Huda; Sari, Wulan Permata (STAI Miftahul Ula Nganjuk, 2025)
This article aims to analyse the relevance of the position of the Supreme Court in relation to the Religious Courts within the national legal system, the role of the Supreme Court in the guidance and supervision of Religious Courts, and the review of the Supreme Court Regulation Number 5 of 2019 on Guidelines for Adjudicating Marriage Dispensation Applications. The approach used in this study is a normative juridical approach with a descriptive-analytical nature. The primary data source in this research is Supreme Court Regulation (PERMA) Number 5 of 2019, while secondary sources include books and articles relevant to the discussion. The data analysis technique employs content analysis. To test the validity of the data, triangulation is used along with an expanded reference base. The research results show that this